2007
DOI: 10.1007/s11746-007-1090-0
|View full text |Cite
|
Sign up to set email alerts
|

Separating Oil from Aqueous Extraction Fractions of Soybean

Abstract: Previous research has shown that enzymeassisted aqueous extraction processing (EAEP) extracts 88-90% of the total soybean oil from extruded full-fat soy flakes into the aqueous media, which is distributed as cream (oil-in-water emulsion), skim, and free oil. In the present work, a simple separatory funnel procedure was effective in separating aqueous skim, cream and free oil fractions allowing mass balances and extraction and recovery efficiencies to be determined. The procedure was used to separate and compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(76 citation statements)
references
References 15 publications
5
70
1
Order By: Relevance
“…Lysophospholipids also present in small amount in G-ZYME G999, resulted in an insignificant increase in the free oil yield. In the case of soybean oil, Lamsal and Johnson (2007) concluded that the use of Phospholipase C resulted in higher free oil yield (73 AE 5%) as compared to the mixture of LysoMaxÔ and G-ZYME G999 at 1:1 ratio (68 AE 9%) under the optimum pH and temperature of the enzymes. Wu et al (2009) have also reported that the use of enzymes shown in Table 5 at their optimum pH and temperature resulted in total deemulsification of the cream emulsions, either the enzymes had been used individually or in combination, or sequentially.…”
Section: De-emulsification Methods For Aqueous Enzymatic Process (Aeed)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lysophospholipids also present in small amount in G-ZYME G999, resulted in an insignificant increase in the free oil yield. In the case of soybean oil, Lamsal and Johnson (2007) concluded that the use of Phospholipase C resulted in higher free oil yield (73 AE 5%) as compared to the mixture of LysoMaxÔ and G-ZYME G999 at 1:1 ratio (68 AE 9%) under the optimum pH and temperature of the enzymes. Wu et al (2009) have also reported that the use of enzymes shown in Table 5 at their optimum pH and temperature resulted in total deemulsification of the cream emulsions, either the enzymes had been used individually or in combination, or sequentially.…”
Section: De-emulsification Methods For Aqueous Enzymatic Process (Aeed)mentioning
confidence: 99%
“…Flow sheet for (a) production of extruded soybean oil by aqueous enzymatic extraction and free soybean oil recovery by aqueous enzymatic emulsion de-emulsification method (Adapted fromChabrand & Glatz, 2009;Lamsal & Johnson, 2007;Wu et al, 2009); (b) production of olive oil by aqueous enzymatic extraction with different post-treatments(Adapted from;De Faveri et al, 2008; Garcia et al, 2001;Ranalli et al, 2001;Ranalli et al, 2003;Ranalli et al, 1999); and (c) production of virgin coconut oil by aqueous enzymatic emulsion de-emulsification method (Adapted fromRaghavendra & Raghavarao, 2010).…”
mentioning
confidence: 99%
“…Since the oleosomes survived intact and floated to the oil layer, oil in the supernatant was probably the result of contamination that could occur when removing the oleosome fraction. Lamsal and Johnson [14] reported that a cocktail of enzymes can achieve a similar effect in the soybean emulsion cream after their aqueous extraction process. Ash and carbohydrate contents did not change when the supernatant were reused in two consecutive protocols with either 0 or 3% enzymes.…”
Section: Chemical Characteristics Of Aqueous Supernatantsmentioning
confidence: 98%
“…Additionally, de Moura et al (2008) recorded higher oil recoveries (93% and 96-97%) from extruded full fat soy flakes when treated with proteases (0.5% w/w Protex 7L-Bacillus amyloliquefaciens and 0.5-1.0% Protex 6L-Bacillus licheniformis, respectively). They, however, observed that very fine grinding of soybean produced a thicker, more viscous emulsion cream phase compared to the emulsion obtained from extruded full fat FFF n/a n/a 50 and 63 240 9.2 46.7 Fullbrook (1983) No enzymes-control flakes which was difficult to separate by centrifugation due to the high emulsion stability of the soy proteins and lecithin (Lamsal and Johnson 2007). In contrast to these studies, other workers have reported no improvements in oil yield by using single and mixed enzymatic systems coupled with aqueous extraction (Marek et al 1990;Rosenthal et al 2001).…”
Section: Enzyme-assisted Extractionmentioning
confidence: 99%